Coordinate differences between static and kinematic precise point positioning: a different approach in spectral analysis during the 2023 Kahramanmara, s earthquake - Karatay, Secil; Erken, Faruk; Pirti, Atinc; Arikan, Feza (ELSEVIER SCI LTD, 2026)
This study investigates effects of static versus kinematic CSRS-PPP processing on coordinate differences (Du Dk Dh) during the 2023 Kahramanmaras, earthquake sequence in Turkiye. GNSS data from TNPGN-Active stations MAR1 and ANTE are analyzed across 10 pre-seismic days (January 28-February 6, 2023) using two approaches: daily spectral analysis with median filtering, detrending and FFT and combined analysis of concatenated time series. Results show processing modes produce discrepancies exceeding 35 % in dominant frequency characteristics and 68 % in spectral variance. We observe a counterintuitive distance paradox: ANTE station exhibits 87.5 % higher baseline frequency variability despite being 46 % farther from the epicenter than MAR1. Statistical analysis (p < 0.001) confirms these differences represent fundamental measurement uncertainties. The height component consistently shows highest processing sensitivity (variance ratios approximate to 2.67), while horizontal components show ratios of 2.2-2.7. During pre-seismic periods, MAR1 demonstrates frequency drift rates of 0.017 mHz/day and ANTE 0.025 mHz/day, suggesting coupling between preparatory earthquake processes and GNSS stability mechanisms. Spectral coherence analysis distinguishes geomagnetically quiet (0.75-0.85), disturbed (0.40-0.50) and pre-seismic (0.55-0.65) conditions, enabling separation of earthquake-related signals from atmospheric artifacts. (c) 2025 COSPAR. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Precise point positioning; Static vs kinematic processing; Spectral analysis; Pre-seismic detection; GNSS monitoring; Earthquake precursors; Geodetic seismology; GPS; GNSS; CONSTRAINTS; SLIP; Engineering; Astronomy & Astrophysics; Geology; Meteorology & Atmospheric Sciences